Direct-drive laser fusion: status, plans and future. (25th January 2021) - Campbell, E. M.; Sangster, T. C.; Goncharov, V. N.; Zuegel, J. D.; Morse, S. F. B.; Sorce, C.; Collins, G. W.; Wei, M. S.; Betti, R.; Regan, S. P.; Froula, D. H.; Dorrer, C.; et al.
Abstract : Laser-direct drive (LDD), along with laser indirect (X-ray) drive (LID) and magnetic drive with pulsed power, is one of the three viable inertial confinement fusion approaches to achieving fusion ignition and gain in the laboratory. The LDD programme is primarily being executed at both the Omega Laser Facility at the Laboratory for Laser Energetics and at the National Ignition Facility (NIF) at Lawrence Livermore National Laboratory. LDD research at Omega includes cryogenic implosions, fundamental physics including material properties, hydrodynamics and laser–plasma interaction physics. LDD research on the NIF is focused on energy coupling and laser–plasma interactions physics at ignition-scale plasmas. Limited implosions on the NIF in the 'polar-drive' configuration, where the irradiation geometry is configured for LID, are also a feature of LDD research. The ability to conduct research over a large range of energy, power and scale size using both Omega and the NIF is a major positive aspect of LDD research that reduces the risk in scaling from OMEGA to megajoule-class lasers. The paper will summarize the present status of LDD research and plans for the future with the goal of ultimately achieving a burning plasma in the laboratory. This article is part of a discussion meeting issue 'Prospects for high gain inertial fusion energy (part 2)'.